The Degree of Marital Compatibility and Family Stability during the Corona Pandemic according to a Number of Variables among a Sample of Married Couples in Irbid Governorate - Awad, Alquran, Nahla Mohammad (Journal of Ecohumanism, 2024)
The study aimed to identify the nature of differences in the degree of marital compatibility and family stability among a sample of married couples in Irbid Governorate according to demographic and personal variables (gender, age, duration of marriage, educational level). The descriptive approach was used for the study, the study sample consisted of (400) husbands and wives from all residents of Irbid Governorate who were drawn randomly. The results of the study showed statistically significant differences at the significance level (α≤0.05) in the field of companionship according to the gender variable, as the value of (F) reached (3.864) with a statistical significance of (0.050) and in favor of males , There are statistically significant differences at the significance level (α≤0.05) in the field of role participation between spouses according to the gender variable, as the value of (F) reached (89.216) with a statistical significance (0.000), in favor of females, there are no statistically significant differences at the significance level (α≤0.05) in the fields (the presence of disorders and the desire for separation and divorce, there are statistically significant differences at the significance level (α≤0.05) in family stability according to the variables (gender - age - duration of marriage - educational level).